Clinical and radiographic evaluation of chloramphenicol-tetracycline-zinc eugenol oxide antibiotic paste in pulp treatment - Fereira, Jesús Luengo; Rivas, Heraclio Reyes; Toscano, Iovanna; Medrano, Luz Elena Carlos; Alvarez, Minerva Anaya (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study has been carried out to evaluate the clinical and radiographic CTZ (Chloramphenicol-Tetracycline-Zinc Eugenol Oxide) antibiotic paste in pulpotomies of primary molars. A Quasi-experimental study in 43 primary molars of children aged 3 to 7 years. Pulpotomies were performed on the selected patients with the CTZ antibiotic paste. Teeth were restored with glass ionomer and preformed steel metal crowns. Clinical and radiographic evaluation was performed at 6 and 12 months. SPSS V-19 program for data analysis and chi-square test was used up to 5%. Success rates were observed during the evaluation periods of time. 93% (x2 = 0.446, p>0.05) and 88.4% (x2 = 0.431, p>0.05) of the clinical form; 97.7% (x2 = 0.534, p>0.05) and 93% (x2 = 0.553, p>0.05) were radiographic, at 6 and 12 months, respectively. The CTZ antibiotic paste is an alternative in the treatment of pulpotomy of molars. It provides an antimicrobial effect, decreased operative time, without causing trauma to the pediatric patient.